2020
DOI: 10.1111/jth.14669
|View full text |Cite
|
Sign up to set email alerts
|

Lupus anticoagulant assay cut‐offs vary between reagents even when derived from a common set of normal donor plasmas

Abstract: Background: Multicenter studies reveal that diagnostic efficacy of lupus anticoagulant (LA) assays is enhanced if cut-offs are locally generated. However, a potential confounder is the inevitable use of separate normal donor populations.Objectives: Generate cut-offs for multiple LA reagents with the same analyzer and normal donor plasmas. Methods:Cut-offs for screen ratio, confirm ratio, percent correction of screen ratio by confirm ratio, and normalized screen/confirm ratio (NSCR) were derived from the same 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…Although ISTH LA detection guidelines recommend 99th percentile cutoffs, it is problematic for many laboratories to source sufficient normal donors for an accurate 99th percentile estimation (>100). Furthermore, other guidelines and studies indicate that, in common with routine coagulation screening assays, LA assay population distributions are commonly Gaussian, or can be made so by data transformation, and that parametric evaluation can be applied on lower donor numbers 5,6,14,33,34,40,41 . All but one of the RRs were Gaussian or successfully transformed, so cutoffs were taken as mean +2 SD, equating to 97.5th percentile for normally distributed data 5,6,34 …”
Section: Discussionmentioning
confidence: 99%
“…Although ISTH LA detection guidelines recommend 99th percentile cutoffs, it is problematic for many laboratories to source sufficient normal donors for an accurate 99th percentile estimation (>100). Furthermore, other guidelines and studies indicate that, in common with routine coagulation screening assays, LA assay population distributions are commonly Gaussian, or can be made so by data transformation, and that parametric evaluation can be applied on lower donor numbers 5,6,14,33,34,40,41 . All but one of the RRs were Gaussian or successfully transformed, so cutoffs were taken as mean +2 SD, equating to 97.5th percentile for normally distributed data 5,6,34 …”
Section: Discussionmentioning
confidence: 99%
“…Probably, they might be explained by the variation in reagent lots, as confirmed in another multicenter study with the same reagent lot used by all participating centers 77 . A more recent study showed poor interlaboratory agreement of cutoff value even when a common set of normal donors were investigated by different platforms 78 . These observations illustrate that because of many variables (eg, sample collection system, sample tubes, demographics of the normal population, variation in PNP, lot of reagents), cutoff values determined elsewhere cannot be transferred irrefutably from one laboratory to another.…”
Section: Preanalytical Analytical and Postanalytical Factors In La Tmentioning
confidence: 93%
“…77 A more recent study showed poor interlaboratory agreement of cutoff value even when a common set of normal donors were investigated by different platforms. 78 These observations illustrate that because of many variables (eg, sample collection system, sample tubes, demographics of the normal population, variation in PNP, lot of reagents), cutoff values determined elsewhere cannot be transferred irrefutably from one laboratory to another. In the meantime, it is still advised to determine in-house cutoff values 73 but joint efforts to calculate universal cutoff values per test/instrument combination should continue, to find a solution for this challenging issue.…”
Section: Cutoff Valuesmentioning
confidence: 99%
“…Полученные результаты приближены к рекомендуемым пороговым значениям (менее 1,2) [3] и соответствуют недавнему исследованию [8] на той же аналитической паре (реагент и анализатор).…”
Section: Discussionunclassified